Analisis Pemakaian Ragam Bahasa dalam Media Sosial Instagram pada Kolom Komentar Influencer Fuji_An - Apridayanti Apridayanti; Emilda Emilda; Syahriandi Syahriandi (STIKes Ibnu Sina Ajibarang, 2025)
This research is to describe the types of language variations in comments on Fuji_an's Instagram account. This research approach is a qualitative approach. This research type is descriptive. The data collection techniques for this research are reading techniques, note-taking techniques, and documentation techniques. The results of the research show that the use of various languages ​​in the comments column of Fuji_an's Instagram account consists of four types of language varieties, namely language varieties in terms of the speaker, language varieties in terms of how to communicate, language varieties in terms of the topic of conversation, and language varieties based on the level of formality. Data from research results found in Fuji_an's Instagram account as many as 50 data consisting of 2 data in terms of the speaker, namely 2 data of official variety and 6 data of unofficial variety 50 data in terms of communication methods, namely written variety data consisting of 2 data of standard written variety and 48 non-standard written variety data 4 data in terms of topic of discussion, namely literary variety 1 data, functional variety 1 data, political and legal variety 1 data, and social variety 1 data 21 data in terms of level of formality, namely intimate variety 7 data, and consultative variety of 2 data.